2015
DOI: 10.1007/s40806-015-0013-9
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Perspectives on the Nature of Sibling Conflict: the Impact of Sex, Relatedness, and Co-residence

Abstract: Our siblings can be our closest allies and yet are often our first rivals. What factors influence the nature of these relationships, and are there certain aspects that make our siblings more likely to be a source of conflict rather than solidarity? From an adaptationist perspective, sibling conflict should vary in frequency and intensity as a function of degree of relatedness. For example, conflict should be most frequent and intense between non-biological and step-siblings while conflict between full biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 26 publications
2
34
2
Order By: Relevance
“…However, these differences almost disappeared with age. This is an interesting finding, indicating that despite the many documented differences between full and half siblings (e.g., Salmon & Hehman, 2015;Tanskanen et al, 2016), geographical differences between full and half siblings are negligible in contemporary Finland, at least on a regional scale. Future research should preferably investigate the topic with more detailed measures of geographical distance.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, these differences almost disappeared with age. This is an interesting finding, indicating that despite the many documented differences between full and half siblings (e.g., Salmon & Hehman, 2015;Tanskanen et al, 2016), geographical differences between full and half siblings are negligible in contemporary Finland, at least on a regional scale. Future research should preferably investigate the topic with more detailed measures of geographical distance.…”
Section: Discussionmentioning
confidence: 78%
“…Close kin tend to have strong social relations throughout their lives (Hamilton, ; Neyer & Lang, ; Rotkirch, ; Salmon & Hehman, ). Family ties are characterised by substantial flows of support and assistance, also in contemporary wealthy and urbanised societies (e.g., Madsen et al, ; Mulder & Kalmijn, ; Stewart‐Williams, ; White & Riedmann, ; Wrzus, Hanel, Wagner, & Neyer, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Salmon and Hehman (2015) found that college students who were living together with siblings had more conflicts with full-than half-siblings. However, compared with these previous studies, the present study has ' (2002) sample was much smaller (n = 192 families) than the large MCS data, and thus they could not restrict the analyses to dual-earner and dual-carer families.…”
Section: Discussionmentioning
confidence: 91%
“…However, compared with these previous studies, the present study has ' (2002) sample was much smaller (n = 192 families) than the large MCS data, and thus they could not restrict the analyses to dual-earner and dual-carer families. As for Salmon and Hehman (2015), they used a small-scale (n = 345 young adults) and non-representative sample of college students. In addition to genetic relatedness, several other factors were found to be associated with sibling conflicts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation